(untitled) (Revista NUPEART, 2020)
This text is based on a conversation circle, entitled: “Imagination and Playfulness”, held in the 1st Conversation Cycle of the Pedagoginga Toy Library, of the Universidade Federal Rural do Rio de Janeiro (UFRRJ) in a virtual way. Thus, a brief experience report is presented that seeks to contribute to building knowledge and expanding the debate on the importance of playing and recreational-creative activities as a result of a pandemic and post-pandemic period. However, after reflecting on the ideas of Lauand (2006), Vigotski (2014) on playfulness and creativity, we conclude that when playing, we open new windows to learn to live together, welcome others and live healthily between laughter and crying. The playful means action and its dimension becomes power when we recreate, we create new worlds around us recovering the experiences we live.